2018
DOI: 10.3390/ijerph15112578
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk in Urbanizing Regions: Examining the Nexus of Infrastructure, Hygiene and Health in Tashkent Province, Uzbekistan

Abstract: Worldwide, development agencies have increased their investments in water supply and sanitation as a “powerful preventive medicine” to address infectious diseases. These interventions have focused on on-site technical interventions or social engineering approaches, emulating the result-based targets of the development goals. Against this backdrop, the study examines the following research question: What is the role of socio-cultural backgrounds, housing characteristics, and environmental hygiene practices in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous studies on the environment and health in Uzbekistan have focused on the Republic of Karakalpakstan [13] and the Tashkent region [14]. Research on the psychosocial health of residents in the Republic of Karakalpakstan demonstrated that the shrinking of the Aral Sea was perceived to contribute to physical symptoms and negative health effects [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the environment and health in Uzbekistan have focused on the Republic of Karakalpakstan [13] and the Tashkent region [14]. Research on the psychosocial health of residents in the Republic of Karakalpakstan demonstrated that the shrinking of the Aral Sea was perceived to contribute to physical symptoms and negative health effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the psychosocial health of residents in the Republic of Karakalpakstan demonstrated that the shrinking of the Aral Sea was perceived to contribute to physical symptoms and negative health effects [13]. According to a study in the Tashkent region, poor sanitation practices were identified as significant predictors of waterborne disease [14]. Research has been conducted on the influence of proximity to industrial areas on congenital diseases, infant mortality, and lung cancer in certain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Housing characteristics are also considered social determinants of health outcomes [ 19 ], and might be associated with sanitation outcomes. For example, recent studies in Uzbekistan and China suggest that certain housing characteristics, such as access to a centralized water supply, are positively associated with improved water-borne illness outcomes and improved sanitation coverage rates [ 20 , 21 ]. Another critical housing characteristic, the amount of dwelling space owned by a family, is important because the toilet design recommended by the Government of India requires 67 ft 2 of land.…”
Section: Introductionmentioning
confidence: 99%